Dietary Adaptations of Early and Middle Pleistocene Equids From the Anagni Basin (Frosinone, Central Italy) - Strani, Flavia; Pushkina, Diana; Bocherens, Hervé; Bellucci, Luca; Sardella, Raffaele; DeMiguel, Daniel (Frontiers in Ecology and Evolution, 2019)
The intermontane Anagni Basin (Frosinone, central Italy) is an important region for Italian biochronology and paleoecology due to the presence of two rich fossil assemblages dated to the Early (Coste San Giacomo) and Middle Pleistocene (Fontana Ranuccio). These sites have yielded a vast collection of large fossil mammals with a well-documented presence of fossil equids in both localities (represented mostly by isolated teeth). Coste San Giacomo is dated to around 2.1 Ma, thereby having recorded the effects of the onset of the Quaternary glacial cycles, which led to a gradual trend towards colder and more arid conditions in the Northern Hemisphere. The fossil equids of this site belong to the first group of grazing stenonid equids of the genus Equus that spread to the Italian Peninsula during the so called "Elephant- Equus" event, which marked the appearance of new large mammals living in herds in open and arid environments. The site of Fontana Ranuccio is dated to around 400 ka, close to the MIS 12 – 11 succession (the "Mid-Brunhes event"), which marked the end of the Middle Pleistocene Transition. The fossil horses from Fontana Ranuccio represent one of the oldest caballoid (or "true horses") populations of the Italian Peninsula. The Anagni Basin, thus, provides important data to investigate paleoecological adaptations of these groups of equids in response to two critical environmental and climatic shifts of the Pleistocene. We explore their niche occupation by examining long-term dental wear patterns and tooth enamel carbon and oxygen stable isotopic composition. Both taxa appear to have exhibited a narrow dietary niche, displaying a clear abrasive (highly specialized) grass-rich diet. In particular, caballoid equids from Fontana Ranuccio show a more abrasion-dominated mesowear signature. Stenonid equids from Coste San Giacomo exploited broader and more diverse landscapes during the Early Pleistocene, whereas caballoid horses from Fontana Ranuccio appeared to have limited their dietary adaptations to a stricter grazing behavior in more closed environments.